The Nature of Chalcogen‐Bonding‐Type Tellurium–Nitrogen Interactions: A First Experimental Structure from the Gas Phase. Issue 3 (17th November 2020) - Glodde, Timo; Vishnevskiy, Yury V.; Zimmermann, Lars; Stammler, Hans‐Georg; Neumann, Beate; Mitzel, Norbert W.
Abstract: (C6 F5 )Te(CH2 )3 NMe2 (1 ), a perfluorophenyltellurium derivative capable of forming intramolecular N⋅⋅⋅Te interactions, was prepared and characterized. The donor‐free reference substance (C6 F5 )TeMe (2 ) and the unsupported adduct (C6 F5 )(Me)Te⋅NMe2 Et (2 b ) were studied in parallel. Molecular structures of 1, 2 and 2 b were determined by single‐crystal X‐ray diffraction and for 1 and 2 by gas‐phase electron diffraction. The structure of 1 shows N⋅⋅⋅Te distances of 2.639(1) Å (solid) and 2.92(3) Å (gas). Ab initio plus NBO and QTAIM calculations show significant charge transfer effects within the N⋅⋅⋅Te interactions and indicate σ‐hole interactions. Abstract : Willing to interact are the tellurium and nitrogen atoms of Me2 N(CH2 )3 Te(C6 F5 ) as was experimentally proven both in the solid state and the gas phase.